EPA-1178 – Father of adolescent girls with anorexia nervosa and bulimia: preliminary results of a qualitative study about their life events and emotional experiences - Garcia, C.; Seidinger, F.M.; Campos, L.K.S.; Turato, E.R. (European psychiatry, 2014)
Eating disorders (ED) are severe psychiatric disorders affecting mainly teenage girls and young women. There is evidence that family aspects play important role in the etiology and outcome of ED. Aspects related to the patients’ father have been poorly studied. To understand emotional experiences and life events of father of adolescent girls diagnosed with anorexia nervosa or bulimia. Qualitative in-depth interviews were carried out with men, fathers of adolescent girls in outpatient treatment at a southern Brazilian general hospital. Sample was composed mostly by men who spent their childhood in the countryside. All of them had lived with their parents at least until the adolescence. Contrary to what clinicians often hear from mothers of ED patients, subjects were concerned about their daughters’ health, wished to see them overcome ED and were well informed about the disorder. They reported that one of the most important events of their lives was their daughter birth. Subjects also reported feeling of powerlessness. They tended to blame the mother for the ED emergence or maintenance, but recognized some relation between the disorder onset and a certain distance in father-daughter relationship. They recognized that their aggressive temper might have interfered with family relationships. Findings may contribute to understand life experiences and emotional characteristics of fathers of ED adolescents and this may help to keep them motivated to the treatment. This understanding can contribute to therapists to help fathers to regain their ability to care for their daughters, getting close to them again and improving father-daughter relationship.